Hubungan Antara Minat Dan Penguasaan Mufradat Terhadap Prestasi Belajar Bahasa Arab Pada Siswa Kelas VII MTs. Mamba’ul Ulum Sumbergedang Pandaan - Nur Rokhmatulloh; Diyah Rahmawati (Impressive: Journal of Education, 2023)
Based on initial observations, the researcher found that there were several obstacles to the process of learning Arabic in schools that were used of research, of them include interest and mastery of Eufrat. So that researchers are interested in doing this research. The purpose of this study was to determine the relationship between interest in learning achievement, to determine the relationship between mastery of Eufrat and learning achievement, and to determine the existence of a significant relationship between two variables simultaneously on the Arabic language learning achievement variable. The research method used is the correlative quantitative method. This is useful for knowing the extent to which the relationship of a variable is related to other variables. And the research instruments used by questionnaires, tests, interviews, documentation, and observations. From the results of this study, the researchers found that there was a positive relationship between variables with a high level of significance, namely 0,000. With the provision that r is calculated with a value of 0,702 while the r tabel has a value of 0,349. Meanwhile, in the calculation of the coefficient of determination, the result is 0,460. This means that the level of relationship between the two independent variables on the dependent variable is 46%. While 54% of learning achievement is influenced by other variables that are not included in the variables studied here.